2013
DOI: 10.1007/s10665-012-9596-3
|View full text |Cite
|
Sign up to set email alerts
|

Strong fragmentation and coagulation with power-law rates

Abstract: Existence of global classical solutions to fragmentation and coagulation equations with unbounded coagulation rates has been recently proved for initial conditions with finite higher order moments. These results cannot be directly generalized to the most natural space of solutions with finite mass and number of particles due to the lack of precise characterization of the domain of the generator of the fragmentation semigroup. In this paper we show that such a generalization is possible in the case when both fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 29 publications
2
15
0
Order By: Relevance
“…This prompted interest in the topic and, subsequently, it was shown that a class of fragmentation operators, that includes physically relevant binary and homogeneous fragmentations, both in the discrete and continuous case, is sectorial albeit in a smaller space of densities that have finite higher moments (the space l 1 p := l 1 U with U = i p , p > 1, or its equivalent X 0,p = L 1 (R + , (1 + x p )dx) in the continuous case), [6,11]. Moreover, for the so-called power law fragmentation it was proven that analyticity holds also in the basic space X 0,1 , [14]. These results also allowed for an explicit characterization of the domains of the fragmentation operator.…”
Section: Some Historymentioning
confidence: 99%
See 1 more Smart Citation
“…This prompted interest in the topic and, subsequently, it was shown that a class of fragmentation operators, that includes physically relevant binary and homogeneous fragmentations, both in the discrete and continuous case, is sectorial albeit in a smaller space of densities that have finite higher moments (the space l 1 p := l 1 U with U = i p , p > 1, or its equivalent X 0,p = L 1 (R + , (1 + x p )dx) in the continuous case), [6,11]. Moreover, for the so-called power law fragmentation it was proven that analyticity holds also in the basic space X 0,1 , [14]. These results also allowed for an explicit characterization of the domains of the fragmentation operator.…”
Section: Some Historymentioning
confidence: 99%
“…We note that (32) cannot hold for p = 1 as ∆ (1) = 0. Nevertheless, there are analytic fragmentation semigroups in l 1 1 and X 0,1 , see [14,60], but the proofs in these spaces require direct estimates of the resolvent that is not explicitly available in general.…”
Section: Fragmentation Equation In Higher Moment Spacesmentioning
confidence: 99%
“…This has changed in the recent few years with the realization that the fragmentation semigroup is analytic for a large class of fragmentation rates a and the daughter distribution functions b. This, in turn, allowed for proving the classical solvability of (1) even if the coagulation rate k is unbounded as long as it is dominated in a suitable sense by the fragmentation rate a, see [7,8] and [5,Section 8.1.2]. The proofs use interpolation spaces between X 0,m and the domain of the generator of the fragmentation semigroup in this space.…”
Section: Introduction Coagulation Equations Introduced By Smoluchowskimentioning
confidence: 99%
“…The main novelty of this article is to show the existence, uniqueness and mass-conserving property of global solutions to (1.1)-(1.2) for singular coagulation and breakup kernels alongwith the quadratic growth on collision kernels. The existence and uniqueness of solutions to the continuous coagulation with linear fragmentation processes have been discussed in many articles by using various techniques for different growth conditions on coagulation and fragmentation rates, see [3,4,5,6,12,19,23,27,29,30,33,34]. However, the nonlinear fragmentation equation has not been extensively addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have already discussed the existence of global classical solutions to the coagulation and linear fragmentation equations through various techniques, see [3,4,5,6,16,22,27,29,30,32]. In [3,4,5,6,27,29,30], authors have discussed the existence of global classical solutions for the coagulation and linear fragmentation equations by using semigroup technique whereas in [16,22,32], a different approach, introduced by Galkin and Dubovskii, is used to show the existence of global classical solutions which relies on a compactness argument. In [22], they have discussed the existence and uniqueness of global solutions to pure coagulation equation by taking an account of unbounded coagulation kernels.…”
Section: Introductionmentioning
confidence: 99%